Enhancing electrochemical nitrogen reduction with Ru nanowires : via the atomic decoration of Pt - Zhang, Weiqing (2022)
Achieving an efficient electrochemical nitrogen reduction reaction (ENRR) remains a great challenge, demanding the development of a new strategy for ENRR catalyst engineering. Herein, we demonstrate a largely improved ENRR by the controlled engineering of Ru nanowires with atomic Pt decoration. Specifically, the readily synthesized Ru88Pt12 nanowires exhibit a high NH3 production rate of 47.1 μg h-1 mgcat-1 and faradaic efficiency of 8.9% at -0.2 V, which are 5.3 and 14.6 times higher than those values for Ru nanowires. They also show outstanding stability, as evidenced by the full preservation of the NH3 yield and faradaic efficiency even after 15 h of electrocatalysis. As revealed by theoretical investigations, the d-band center of Ru atoms is upshifted by the tensile strain due to the presence of Pt atoms, leading to the selective enhancement of N2 adsorption and the stabilization of N2H∗. Such an atomic engineering method may be applied to precisely tailor other metal nanocatalysts for different applications.